2016
DOI: 10.1016/j.eneco.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the adoption of photovoltaic systems in Flanders

Abstract: We study the determinants of PV adoption in the region of Flanders (Belgium), where PV adoption reached high levels during 2006-2012, because of active government intervention. Based on a unique dataset at a very detailed spatial level, we estimate a Poisson model to explain the heterogeneity in adoption rates. We obtain the following findings. First, local policies have a robust and significant impact on PV adoption, providing indirect evidence that the larger regional incentives formed the basis for the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 36 publications
(67 reference statements)
5
61
0
Order By: Relevance
“…There are many driving forces for solar technology uptake other than policy. Prior studies have found a positive impact of income on uptake of household solar PV (De Groote et al, 2016;Kwan, 2012) and solar water heaters (Aydin et al, 2018). Using a survey approach, Bondio et al (2018) concluded that solar PV uptake in Queensland is most popular among the middle class.…”
Section: Contributionsmentioning
confidence: 99%
“…There are many driving forces for solar technology uptake other than policy. Prior studies have found a positive impact of income on uptake of household solar PV (De Groote et al, 2016;Kwan, 2012) and solar water heaters (Aydin et al, 2018). Using a survey approach, Bondio et al (2018) concluded that solar PV uptake in Queensland is most popular among the middle class.…”
Section: Contributionsmentioning
confidence: 99%
“…De Groote et al [41] investigated the heterogeneity in the adoption of the photovoltaic system in the region of Flanders (Belgium). The author explained that important housing characteristics such as house size, roof insulation, and quality of the roof are positively correlated with the solar photovoltaic installation.…”
Section: Literature From Empirical Research Workmentioning
confidence: 99%
“…Similarly, the type and size of the house are expected to positively affect SHS adoption. Some studies found that the number of rooms of houses has a positive correlation with solar home system adoption [41,6]. Prior information or knowledge that households have about the solar home system is considered as one driving factor of solar energy adoption [32].…”
Section: Identification Of Explanatory Variablesmentioning
confidence: 99%
“…[52] analyzed the effect of social influences concerning economic and ecological issues in the adoption of photovoltaic technology in Germany. Additionally, studies examined factors and their impact on the acquisition of solar renewable energy technologies for urban households in Mexico [53] and identified the determinants of photovoltaic energy acquisition in Belgium [54]. In the Flanders region, Germany, and Canada, the study by Ref.…”
Section: Introductionmentioning
confidence: 99%